Kemukjizatan Bahasa dalam Al-Qur’an : Analisis linguistik dan fonologi terhadap faahsilah dalam Al-Qur’an - Nurul Istianah Ruddin; Achmad Abubakar; Sitti Aisyah Chalik (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The Qur'an is a book of God known for the depth of its message and the beauty of its language. One of the aesthetic aspects of the Qur'anic language that is its miracle is fawashil, namely words or phrases at the end of verses. Fawashil is the plural of the word Fashilah in the Qur'an, which plays an important role in the beauty, structure, and meaning of the verses of the Qur'an. This study aims to analyze the linguistic miracle that focuses on fashilah in the Qur'an and its correlation with the phonology of the sound of the last verse. This study also educates readers of the Qur'an that in reciting the end and beginning of verses, they can understand the rules and meanings contained therein. Arranging the rhythm, stop signs (waqaf) and the beginning of a verse (ibtida') are basic things that must be considered in reciting the verses of the Qur'an. The methodology used in this research is a literature review using a qualitative design with an analytical approach. The results of this study show that the definition of fluency in the Quran differs from that of qafiyah (poetry), as fluency is not a fabrication or creation of man, but rather part of the miracle of the Quran's words and meaning. Meanwhile, fluency from a phonological perspective is highly relevant because it is related to the sounds of letters or words at the end of verses in the Quran, creating rhythm and rhythm, which are among the linguistic miracles of the Quran.